1998
DOI: 10.1021/bi980915e
|View full text |Cite
|
Sign up to set email alerts
|

Sphingomyelinase Induces Lipid Microdomain Formation in a Fluid Phosphatidylcholine/Sphingomyelin Membrane

Abstract: The behaviors of two chemically well-defined sphingolipids, N-palmitoyl-sphingomyelin (C16:0-SM) and the corresponding ceramide (C16:0-Cer), in a 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphatidylcholine (POPC) matrix were compared. Minor attenuation of lateral diffusion upon increasing the mole fraction of C16:0-SM (XSM, up to 0.25) was indicated by the slight decrement in the excimer/monomer intensity ratio (Ie/Im) for a trace amount (mole fraction X = 0.01) of a pyrene-labeled ceramide analogue (N-[(pyren)-1-yl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
261
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(279 citation statements)
references
References 45 publications
17
261
1
Order By: Relevance
“…This possibly indicates a saturation of particular membrane insertion sites. Once in the membrane, C 6 -SM might not be randomly dispersed but, like natural long-chain sphingolipids, show a tendency to selfaggregate in the plane of the membrane (van Blitterswijk et al, 1987(van Blitterswijk et al, , 2003Holopainen et al, 1998). It is therefore appealing to speculate that these physical properties allow C 6 -SM to form their own 'artificial' rafts, which, however, remain detergent soluble (as found here).…”
Section: Propidium Iodidementioning
confidence: 60%
“…This possibly indicates a saturation of particular membrane insertion sites. Once in the membrane, C 6 -SM might not be randomly dispersed but, like natural long-chain sphingolipids, show a tendency to selfaggregate in the plane of the membrane (van Blitterswijk et al, 1987(van Blitterswijk et al, , 2003Holopainen et al, 1998). It is therefore appealing to speculate that these physical properties allow C 6 -SM to form their own 'artificial' rafts, which, however, remain detergent soluble (as found here).…”
Section: Propidium Iodidementioning
confidence: 60%
“…It is conceivable that generation of ceramide increases membrane¯uidity and raft formation, thereby facilitating receptor signaling (Holopainen et al, 1998;Zundel et al, 2000). Indeed, recent studies showed that ceramide may be critically involved in cap formation and clustering of the CD95 receptor Cremesti et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Ceramide molecules self-associate to small ceramide-enriched membrane microdomains, which have the tendency to spontaneously fuse to large ceramide-enriched membrane domains [36-38]. The formation of ceramide-enriched membrane domains was shown to occur in cells after stimulation via a variety of stimuli including CD95 [39-41], CD40 [42], DR5 [43], FcγRII [44], the PAF-receptor [45], but also after infection with P. aeruginosa [19], Neisseriae gonorrhoeae [46] , Rhinovirus [47], application of stress stimuli such as UV-light [48], cisplatin [49] or Cu 2+ -treatment [50].…”
Section: Ceramidementioning
confidence: 99%